Developing Pop-Up Book Digital as Learning Media of Procedure Text: Student’s Learning Style - Sahara, Siti; Nailah; Saragih, Anggraini Thesisia; Pelawi, Fauziah Br. S (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
The research aim to obtain the learning style of seven grade students at SMP Pahlwan Medan. The result gained from this study are used to develop Pop-Up Book Digital as learning media which appropriate based on student’s need. This research method used the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). But researchers limit this study only to the analysis stage where to analyzed student’s learning style as the first stage. The data collection technique is in the form of a questionnaire and have been given to 27 students. The result of this study shows that the majority of students, namely 32.8%, have a visual learning style, then 32.6% have an auditory learning style, and 21.5% have a kinesthetic learning style. Keywords: Pop up book digital, Learning style, Procedure Text